Connection fiscal decentralization and poverty in South Sulawesi: Analysis of the 2004–2024 period - Ihsan Ashari; Tuti Adi Tama; Dwi Hastuti Lestari Komarlina (Priviet Social Sciences Journal, 2026)
This study highlights both direct and indirect linkages mediated by economic growth, as it investigates the effects of fiscal decentralization on poverty levels in South Sulawesi Province between 2004 and 2024. The General Allocation Fund (DAU), Special Allocation Fund (DAK), Revenue Sharing Fund (DBH), and Local Own-Source Revenue (PAD) are the four main fiscal mechanisms that are the focus of this study. Using route analysis with time-series data in SPSS, this study reveals several important findings. Poverty levels are significantly negatively impacted by economic growth. As a mediating variable, DAU shows a strong positive relationship with poverty, but DAK and PAD show notable negative relationships. DBH, on the other hand, does not demonstrate a noteworthy indirect impact on poverty via the conduit of economic expansion. The findings suggest that the efficacy of fiscal decentralization in alleviating poverty varies among different fiscal instruments, with DAK and PAD yielding the most beneficial results when implemented in programs that foster economic growth. These insights provide critical guidance for policymakers aiming to enhance the effectiveness of fiscal decentralization strategies in combating poverty in South Sulawesi Province.